Evaluating the quality of evidence for intelligent tutoring systems in the tutoring of math for children aged 6 to 12 : a systematic review - Cheng, Janice Shu Hui (Nanyang Technological University, 2020)
The present systematic review gathered and evaluated the quality of evidence in empirical studies that analysed the effectiveness of Intelligent Tutoring Systems (ITSs) in the tutoring of mathematics to primary school students between the ages of 6 and 12 years old. As a follow up to a previous meta-analysis done in 2013, reports were taken from a five-year period between 2014 and 2019. Out of the 664 unique studies gathered, only 14 studies made it to the qualitative analysis stage after meeting all the inclusion criteria. From these 14 studies, 4 of them showed “sufficient” evidence to support their findings on the incorporation of ITSs into mainstream classrooms, but went on to score poorly on other additional quality indicators. Our main findings are as follows: (a) there has been insufficient research conducted that focuses on ITS incorporation in primary school teaching frameworks for mathematics, and (b) the quality of evidence among the existing studies is severely lacking. The present study’s findings highlight the need for more research to be done in the field of mathematical ITSs, especially among primary school children between the ages of 6 and 12 years old, but also for better research practices to be adopted in the field of educational psychology. In addition to conducting more research in non-Western societies, future research in the field should consider evaluating individual features of ITSs to determine how they may affect the overall effectiveness of ITS incorporation into mainstream teaching frameworks.